Catalysts of 3D ordered macroporous ZrO2-supported core–shell Pt@CeO2−x nanoparticles: effect of the optimized Pt–CeO2 interface on improving the catalytic activity and stability of soot oxidation. Issue 4 (7th February 2017) - Li, Yazhao; Du, Yuhao; Wei, Yuechang; Zhao, Zhen; Jin, Baofang; Zhang, Xindong; Liu, Jian
Abstract : The catalytic performance of 3D-OM Pt1.0 @CeO2− x /ZrO2 -1 is better than that of 3D-OM Pt1.0 /ZrO2 . Abstract : We successfully synthesized 3D ordered macroporous (OM) Pt@CeO2− x /ZrO2 catalysts by a co-precipitation method. This series of catalysts have a well-defined 3D-OM structure. We investigated the activity of the 3D-OM Pt@CeO2− x /ZrO2 catalysts with different shell thicknesses, and systematically studied the adsorption and desorption of NO on the 3D-OM Pt@CeO2− x /ZrO2 via in situ DRIFTS. The 3D-OM support enhances the contact efficiency between the solid reactant and catalyst, while the Pt@CeO2− x core–shell nanoparticles with strong Pt–CeO2− x interaction lead to a larger number of active species. With increasing the Ce/Pt molar ratio, the thickness of the shell becomes larger and the activity of Pt@CeO2− x /ZrO2 becomes lower. Among the as-prepared core–shell catalysts tested, the 3D-OM Pt1.0 @CeO2− x /ZrO2 -1 catalyst with the proper thickness of CeO2− x nanolayer shell showed the highest catalytic activity for soot combustion.